Exploring the sex dimorphism in the expression of intestinal barrier and immune-related genes and intestinal microbiota in cage-cultured large yellow croaker (Larimichthys crocea) during the overwintering period along the Zhoushan coast - Cen, Haoxiong; Li, Haidong; Chen, Ruiyi; Hu, Weihua; Yang, Yang; Li, Weiye; Yin, Xiaolong; Liu, Bingjian; Xu, Dongdong (Frontiers in Marine Science, 2024)
In Zhejiang province, large yellow croakers are primarily cultured in net cages, facing significant challenges during the overwintering period such as susceptibility to cold and starvation stress. Notably, the observable sexual dimorphism in the large yellow croaker hints at the likelihood of gender differences in their responses to these environmental stresses. However, the potential sex-specific adaptive changes during overwintering remain unexplored. To gain deeper insights, we investigated the expression of intestinal barrier-related genes, immune responses, and changes in intestinal microbiota during the overwintering period in males and females separately. The results revealed a more pronounced loss of body weight in females than that in males. In male intestines, there was a significant decrease in the expression of intestinal barrier-related genes (arp2/3, occludin, and zo1), contrasting with a significant increase in females. The expression of TLR1, TLR3, TLR7, TLR9, MyD88, and NF-κB genes in the intestines of female fish decreased significantly in March compared to November, while the opposite trend was observed in male fish. However, in the liver, TLR1, TLR3, TLR7, TLR9, MyD88, and NF-κB genes expression were both decreased significantly in males and females. In the male intestines, there was a significant increase in the expression of inflammatory cytokine genes (IL-1β and IL-6). In the females, IL-1β gene expression significantly decreased, while IL-6 expression increased significantly. The expression of IL-10 genes decreased in both males and females. In the liver, both the males and females exhibited a significant increase in the expression of IL-1β and IL-6 genes. Further analysis revealed greater susceptibility of male intestinal microbiota diversity during the overwintering period. Firmicutes’ relative abundance exhibited opposing changes between the males and females, and Proteobacteria abundance, driven by a significant increase in Vibrio bacteria, significantly increased in the males. In conclusion, the overwintering period may compromise the structural integrity of male fish intestines, reducing their immune function. Additionally, the response strategy of the intestinal microbiota differs between sexes. The findings provide crucial insights for crafting effective strategies and management decisions in cage-cultured large yellow croaker during the overwintering period, as well as offering theoretical references for monosex aquaculture.